Mira Variables In The Dfbs Catalogue Of Late-Type Stars - Gigoyan, K. K.; Gigoyan, K. S.; Sarkissian, A.; Meftah, M.; Keckhut, P.; Paronyan, G.; Rahmatullaeva, F.
We present phase-dependent ASAS-SN light curves, periods and spectral classes for seven Mira-type variables, based on Gaia DR3 BP/RP low-resolution spectra. We also present their spectral energy distributions (SEDs), mass ranges, mass-loss rates, Galactic plane positions, and other important astrophysical parameters. These stars are included in the "Value-Added Catalogue of Late-Type Stars Found in the Digitized First Byurakan Survey Database" (Third Edition).
Keywords: Astrophysics